TAPT1—at the crossroads of extracellular matrix and signaling in Osteogenesis imperfecta - Julia Etich; Oliver Semler; Nicola L Stevenson; Alice Stephan; Roberta Besio; Nadia Garibaldi; Nadine Reintjes; Claudia Dafinger; Max Christoph Liebau; Ulrich Baumann; Matthias Mörgelin; Antonella Forlino; et al. (EMBO Molecular Medicine)
Graphical Abstract Osteogenesis imperfecta (OI) is a hereditary skeletal disorder primarily affecting collagen type I structure and function, causing bone fragility and occasionally versatile extraskeletal symptoms. This study expands the spectrum of OI‐causing TAPT1 mutations and links extracellular matrix changes to signaling regulation.